Use of Squeeze‐Induced Somnolence for Routine Plasma Administration in Healthy Neonatal Foals. (September 2014) - Pickles, K.J.; Madigan, J.E.; Torske, S.; Aleman, M.R.
Abstract : Reasons for performing study: A nonchemical method of restraint to facilitate neonatal foal handling and minimally invasive procedures would be highly useful. Objectives: To investigate squeeze‐induced somnolence for providing adequate restraint of healthy neonatal foals for the purpose of plasma administration. Study design: Prospective clinical study. Methods: Squeeze‐induced somnolence of neonatal foals was performed by use of a soft rope restraint as previously described [1] to allow intravenous catheterisation and plasma administration. Physiological and clinical parameters were monitored pre‐, during and post squeeze‐induced somnolence. Results: Squeeze‐induced somnolence and plasma administration was performed on 14 foals within the first day of life without any adverse effects. Mean time to recumbency during squeeze restraint was 53 s, mean time to stand and mean time to nurse from dam following release of restraint were 46 s and 163 s, respectively. Over 50% of foals gave some reaction to subcutaneous injection of local anaesthetic but only one foal reacted strongly. The restraint technique was performed without any difficulty in 8/14 foals, 5/14 foals became less somnolent latterly in the procedure (around 17–18 min) and one foal never became fully somnolent. Conclusions: Squeeze‐induced somnolence provides adequate restraint for plasma administration, without the need for sedation, in the majority of neonatal foals. Squeeze‐induced somnolence can be used to allow nonchemical restraint of neonatal foals for routine procedures. Further refinement of the technique is required to maximise its potential usefulness. Ethical animal research: The study was approved by the University of California Institutional Animal Care and Use Committee. Foals were included in the study with informed owner consent.Sources of funding: Private anonymous donation.Competing interests: None.